2011
DOI: 10.1186/1297-9686-43-43
|View full text |Cite
|
Sign up to set email alerts
|

A common reference population from four European Holstein populations increases reliability of genomic predictions

Abstract: BackgroundSize of the reference population and reliability of phenotypes are crucial factors influencing the reliability of genomic predictions. It is therefore useful to combine closely related populations. Increased accuracies of genomic predictions depend on the number of individuals added to the reference population, the reliability of their phenotypes, and the relatedness of the populations that are combined.MethodsThis paper assesses the increase in reliability achieved when combining four Holstein refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
191
3
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(209 citation statements)
references
References 19 publications
9
191
3
6
Order By: Relevance
“…PS scheme) resulted in a clear reduction of per generation inbreeding rates compared with PT schemes, for only slight modifications of the generation interval (Pryce et al, 2010;de Roos et al, 2011;Lillehammer et al, 2011;Buch et al, 2012a). Setting up JS schemes also generally led to reductions in per generation DF compared with PT schemes.…”
Section: New Opportunities To Monitor and Preserve Genetic Diversitymentioning
confidence: 94%
See 1 more Smart Citation
“…PS scheme) resulted in a clear reduction of per generation inbreeding rates compared with PT schemes, for only slight modifications of the generation interval (Pryce et al, 2010;de Roos et al, 2011;Lillehammer et al, 2011;Buch et al, 2012a). Setting up JS schemes also generally led to reductions in per generation DF compared with PT schemes.…”
Section: New Opportunities To Monitor and Preserve Genetic Diversitymentioning
confidence: 94%
“…Therefore, genomic selection is expected to reduce the weight of family information in selection decisions by placing the emphasis on Mendelian sampling information of young candidates (Daetwyler et al, 2007). The largest reductions in inbreeding rates due to the use of genomic selection were observed for traits of low heritability (Lillehammer et al, 2011) and when a large part of variance was explained by markers (de Roos et al, 2011). By screening a large population of candidates, genomic selection also facilitates the identification of the least related animals having high genetic merit with a higher accuracy than before.…”
Section: New Opportunities To Monitor and Preserve Genetic Diversitymentioning
confidence: 99%
“…For European dairy cattle populations, Lund et al (2011) reported a gain in reliability between 2% and 13% for protein yield when a joint reference population consisting of Norwegian, German, French and Dutch Holstein Friesian bulls was compared to the results from the separate national reference populations. Sharing genotypes has been shown to be especially profitable if one population has a very small size.…”
Section: Combining Populations From Different Countries or Different mentioning
confidence: 99%
“…These international genetic evaluations (i.e. MACE evaluations) can subsequently be included in national genomic evaluations (Lund et al, 2011). Hence, a bull born in a foreign country may receive an estimated breeding value in all countries despite having no progeny in those countries and therefore once a genotype is available, the sire can be included in the reference population of the national genomic evaluations using his INTERBULL breeding value.…”
mentioning
confidence: 99%